2006
DOI: 10.1177/1049731505284863
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Interventions for Foster Children: A Systematic Research Synthesis

Abstract: Approximately 30% of children in foster care have severe emotional, behavioral, or developmental problems. A systematic research synthesis of empirical studies was conducted in an attempt to identify and classify therapeutic interventions for foster children. Utilizing a treatment protocol classification system, empirical studies were classified according to their theoretical, clinical, and empirical support. A total of 18 studies were reviewed, including a compare and contrast of methodological strengths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 46 publications
0
71
0
Order By: Relevance
“…Psychologists do not recommend them, and therapists do not mention them among the services they provide. This scenario stands in tension with the recommendations of a number of organizations and experts who call for bringing evidencebased mental health care to system consumers (Marsenich 2002;Saunders et al 2003;Chadwick Center on Children and Families 2004;Wulczyn et al 2005;Craven and Lee 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists do not recommend them, and therapists do not mention them among the services they provide. This scenario stands in tension with the recommendations of a number of organizations and experts who call for bringing evidencebased mental health care to system consumers (Marsenich 2002;Saunders et al 2003;Chadwick Center on Children and Families 2004;Wulczyn et al 2005;Craven and Lee 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the pressing mental health needs of youth in foster care, a recent review of the literature found a lack of mental health services designed specifically for this population (Craven and Lee 2006). Craven and Lee (2006) surveyed 18 interventions that mentioned foster children in the study, but only six were specifically designed for the foster care population.…”
Section: Review Of Treatments For Youth In Foster Carementioning
confidence: 99%
“…Craven and Lee (2006) surveyed 18 interventions that mentioned foster children in the study, but only six were specifically designed for the foster care population. Interestingly, all 18 interventions met the ''supported and acceptable'' criteria or higher (Craven and Lee 2006); which begged the question, are specialized services needed to treat foster youth? Stated differently, perhaps clinically sound traditional services can address the needs of foster youth with emotional and behavioral difficulties.…”
Section: Review Of Treatments For Youth In Foster Carementioning
confidence: 99%
See 1 more Smart Citation
“…emotional, behavioral, or developmental challenges stands at approximately 30% (Craven & Lee, 2006). At the same time, the demand to use less restrictive environments (i.e., therapeutic foster care [TFC] vs. residential treatment) to care for and treat emotionally and behaviorally challenged foster care children and youth continues to grow.…”
mentioning
confidence: 99%